Spending Behaviour of Gen Z Consumers in the Use of Digital Payment Systems - Lamichhane, Koshish Jung (Journal of Business and Social Sciences Research, 2025)
This study investigates the excessive spending behaviour of Gen Z consumers in Kathmandu Valley when using digital payment systems, applying Transcendental Phenomenology and thematic analysis. Unlike existing research using models like TAM and UTAUT, this study delves into behavioural drivers of overspending. Five key themes emerge: spending management challenges, digital payment influences, spending triggers, and mitigation strategies. Findings reveal that the intangibility of digital transactions, illusion of liquidity, and lack of “pain of paying” contribute to overspending. Triggers include promotional offers, ease of use, peer influence, and event-driven deals. Mitigation strategies involve financial literacy, visual spending cues, and personalised alerts. Data were collected through semi-structured interviews with seven participants and focus group discussions with three Gen Z student cohorts using purposive sampling and Moustakas’ phenomenological approach. The study emphasises the need for tailored interventions in digital platforms, such as enhanced user education and system design improvements. Though limited to Kathmandu Valley, the findings lay groundwork for broader research on digital financial behaviour.